Effect of epipleural blockade on the management of nephritis in buffaloes - SHARDA, RAJU; KUMAR, AMRESH; JADON, N S (The Indian Journal of Animal Sciences, 2014)
Epipleural blockade with 0.5% solution of lignocaine hydrochloride alongwith parenteral enrofloxacin (floxldin) in experimental nephritis in buffalo calves showed an early recovery as compared to the treatment with lignocaine hydrochloride and enrofloxacin alone. The physiological parameters (heart rate, respiratory rate and temperature) returned to near normal level by day 10 and haematological parameters (total erythrocyte count, haemoglobin, packed-cell volume, total leucocyte count and differential leucocyte count,) by day 13 in animals given epipleural block alongwith antibiotics as compared to day 16 and 21 in antibiotic and epipleural block alone administered animals. Various biochemical parameters (creatinine, BUN, total protein, albumin, urinary GGT, alkaline phosphatase) returned to base level by day 16 in animals given epipleural block along with antibiotics as compared to day 21 in epipleural block and antibiotic alone administered animals.